PERAN PEMERINTAH DESA DALAM PENGEMBANGAN DESA WISATA EDUKASI GERABAH - Dian Ayuningtyas; Hesti Lestari; Dewi Rostyaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
The pottery education tourism village is an innovation by the village youth that aims to preserve the pottery potential of Rendeng Village. This tourist village was developed by the Rendeng Village Government because the potential for pottery produced by residents is very large to help the community's economy. This study aims to analyze the role of village governments in the development of tourism villages and analyze the supporting and inhibiting factors of the role of village governments. The type of research is descriptive qualitative, with techniques through interviews, observations, and documentation. The results of the study show the role of the Rendeng Village Government as a social animation, namely providing extensive opportunities for BUMDes and Karang Taruna and initiating tourism development programs; mediation and negotiation, namely holding village rembug and socialization; providing support, namely conducting coaching and moral support to citizens; group facilitation, namely building infrastructure; utilization of resources and skills, namely carrying out coaching and training to the community; and the role of organizing, namely monitoring and evaluating village community organizations. This role has not been fully optimized because there are obstacles related to the low level of education of some residents, limited funds, and the absence of village regulations. Researchers provide advice to village governments to conduct coaching and training; seek financial assistance and establish cooperation with outside investors; and immediately create a legal basis related to tourism villages.